The Judgement Machine: Markets, Internet Technologies and Policies in Commercial Sex. Issue 1 (27th August 2014) - Pettinger, Lynne
Abstract : The judgements and valuations made on Internet review sites are part of contemporary consumer culture. This article considers what such sites do in the market for commercial sex. It contributes to policy discussions in two ways. Firstly, it considers how the infrastructure and mechanisms of the web enables organising, searching and reporting of consumer experience, and hence how web reviews mediate commercial markets. It thereby draws links between social policies that concern the Internet and those that relate to sex work. Secondly, it explores how sex review sites mediate the field of commercial sex and discusses some of the potential insights for policy audiences. Policies directed at the regulation of this market will benefit from clear recognition of what customers understand their actions to be and how they participate in the construction of norms about commercial sex.